Swimmers` effective actions during the backstroke start technique - de Jesus, K.; de Jesus, K.; Mourão, L.; Roesler, H.; Fernandes, R. J.; Vaz, M. A. P.; Vilas-Boas, J. P.; Machado, L. J. (Sensors, 2023)
The analysis of the external forces of swimming starts has revealed how swimmers propel themselves out of the block, but data should be properly interpreted to fully understand force-generation mechanisms. This study aimed to assess horizontal and vertical forces in the backstroke start based on swimmers` structural and propulsive actions. Firstly, a simulated structural force was estimated by two transient backstroke-start inter-segmental realistic body positions: a maximally tucked position and an extended one (just before the hands-off and the take-off, respectively). Secondly, 10 competitive backstroke swimmers performed four 15 m maximal backstroke starts with the external forces estimated. Thirdly, the simulated structural force was subtracted from raw horizontal and vertical force data, measured between hands-off and take-off instants, resulting in the propulsive forces. The application of the algorithm has evidenced that backstrokers` horizontal and vertical simulated-structural-force components contributed to ~40% of total force during start propulsion (~0.2-0.12 s before the take-off), followed by the propulsive horizontal force increment and a progressive vertical component reduction (~0.05 s) with ~20° take-off angle. Based on these findings, researchers and coaches can better guide swimmers as to the proper mechanical strategies to achieve effectiveness in the backstroke start, and to improve direct transfer of resistance training programs.